Existence of one non‐trivial anti‐periodic solution for second‐order impulsive differential inclusions. (20th February 2017) - Hadjian, Armin; Heidarkhani, Shapour
Abstract : The existence of one non‐trivial solution for a second‐order impulsive differential inclusion is established. More precisely, a recent critical point result is exploited, in order to prove the existence of a determined open interval of positive eigenvalues for which the considered problem admits at least one non‐trivial anti‐periodic solution. Copyright © 2017 John Wiley & Sons, Ltd.